2015
DOI: 10.1007/s11105-015-0864-z
|View full text |Cite
|
Sign up to set email alerts
|

Squalene Synthase Gene from Medicinal Herb Bacopa monniera: Molecular Characterization, Differential Expression, Comparative Modeling, and Docking Studies

Abstract: The widespread pharmaceutically important triterpenoid saponins are synthesized via isoprenoid pathway. The formation of squalene is the key regulatory point in triterpene biosynthesis, catalyzed by squalene synthase (SQS). The present study deals with the detailed characterization of SQS by molecular, biochemical, and computational means from Bacopa monniera, an immensely important medicinal plant rich in triterpenoid saponin, bacosides. A full-length SQS gene was isolated from B. monniera, characterized as B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…BmSQS mRNA expression level was found to be higher in vegetative parts (roots) as compared to floral parts. Methyl jasmonate induces the BmSQS mRNA expression in all tissues tested, while salicylic acid, cold, and salt induce much higher expression in roots 97 . Comparative transcriptome analysis of shoot and root tissue of Bacopa monnieri identifies potential genes related to triterpenoid saponin biosynthesis.…”
Section: Analysis Of Metabolic Pathway Gene Expressionmentioning
confidence: 89%
“…BmSQS mRNA expression level was found to be higher in vegetative parts (roots) as compared to floral parts. Methyl jasmonate induces the BmSQS mRNA expression in all tissues tested, while salicylic acid, cold, and salt induce much higher expression in roots 97 . Comparative transcriptome analysis of shoot and root tissue of Bacopa monnieri identifies potential genes related to triterpenoid saponin biosynthesis.…”
Section: Analysis Of Metabolic Pathway Gene Expressionmentioning
confidence: 89%
“…Domains I, II, and III are involved in the first step of SS biosynthesis; domain IV participates in the second step; domain VI is a hydrophobic region that binds to the endoplasmic reticulum. The Mg 2+ -binding aspartate-rich regions and amino acids in the active site (Asp77, Asp81, Tyr168, Asp213, and Asp217) were highly conserved in SS amino acid sequences among different plant species [37][38][39]. Previously, it has been shown that overexpression of the SS (AB115496) gene significantly increases the ginsenoside content [40] in Panax ginseng.…”
Section: Discussionmentioning
confidence: 99%
“…The MVA pathway initiates with the acetyl-coenzyme A, which condenses into the acetoacetyl-CoA by the catalyzing action of acetyl-CoA acetyltransferase. Acetyl-coenzyme A is converted to isopentenyl diphosphate (IPP) through MVA, and HMGR (HMG-CoA reductase) which finally supplies carbon for the bacoside biosynthesis 17 18 . In the present investigation, both the microbes upregulated the expression of HMGR , a post-transcriptionally as well as post-translationally regulated gene responsible for catalyzing the conversion of HMG-CoA to mevalonate 19 .…”
Section: Discussionmentioning
confidence: 99%